Pemahaman dan Implementasi Wakaf sebagai Instrumen Sosial dan Ekonomi dalam Islam - Amin, M. Misbahul; salsabila sukma, Najma (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
Waqf is a significant social and economic instrument in Islam aimed at achieving the welfare of the ummah. As a means of wealth distribution, waqf benefits not only individuals or specific groups but also serves broader societal interests. In addition to public waqf, there is family waqf (waqf ahli) directed towards specific beneficiaries as determined by the waqif (donor). This study employs a theoretical approach to analyze the concepts, foundational principles, objectives, and benefits of waqf in Islam. The findings reveal that, despite its substantial potential to create positive impacts, the implementation of waqf often does not fully align with Islamic principles. This highlights the need for further education about waqf regulations and management in accordance with Sharia to maximize its benefits. This research aims to enhance public understanding of the critical role of waqf in social and economic development while promoting more effective waqf management to achieve the intended welfare objectives for the ummah.